Genetic counseling does not fulfill the counselees' need for certainty in hereditary breast/ovarian cancer families: an explorative assessment. Issue 5 (9th July 2012) - Vos, Joël; Menko, Fred H.; Oosterwijk, Jan C.; van, Christi J.; Stiggelbout, Anne M.; Tibben, Aad
Abstract Background Many cancer‐patients undergo DNA testing in the BRCA1/2 genes to receive information about the likelihood that cancer is heritable. Previous nonsystematic studies suggested that DNA testing often does not fulfill the counselees' needs for certainty. We explored the balance between the counselees' need for certainty and perceived certainty (NfC‐PC, i.e., level of fulfillment of NfC) regarding the specific domains of DNA test result, heredity and cancer. We also examined relationships of NfC‐PC with coping styles and distress. Method Before disclosure of BRCA1/2 test results for hereditary breast/ovarian cancer (T1), questionnaires were filled in by 467 cancer‐patients. Another questionnaire (T2) was filled in after disclosure of pathogenic mutation results (n = 30), uninformative results (n = 202) or unclassified‐variants (n = 16). Results Before and after DNA test result disclosure, overall 58–94% of all counselees experienced unfulfilled NfC regarding the DNA test result, heredity and cancer. Compared with T1, the communication of pathogenic mutations (T2) caused more fulfillment of the NfC about the DNA test result, but less about cancer and heredity (p < .01). Compared with T1, unclassified variants (T2) did not significantly change the extent of fulfillment of all counselees' needs for certainty (NfC > PC). Compared with T1, uninformative results (T2) caused more fulfillments of all needs than before disclosure (p < 0.01). Counselees differentiated NfC and PC between the domains of DNA‐test result, heredity and cancer ( p < 0.01). The unfulfilled needs for certainty (NfC‐PC) were uncorrelated with cognitive understanding of the DNA test result. Conclusion The counselees' NfC needs more attention in research and practice, for example, when the potential uncertainties of testing are discussed. The counselees' NfC may be assessed and used in tailored, mutual communication of DNA test results. Copyright © 2012 John Wiley & Sons, Ltd.